The Great European Powers and Balkan Wars 1912-1913 - Rubacha, Jarosław (Balcanica Posnaniensia. Acta et studia, 2012)
Balkan Wars 1912-1913 were a milestone event in the history of the Balkans. They ending, started in 1878, process of expulsion of Turkey from its European possessions, and creating the possibility of realizing popular in this part of Europe slogan “The Balkans for the Balkan nations”. It should be noted that taking on the Balkan Peninsula events were with attention watched by the European great powers, because this part of Europe they are treated as a region of special economic and politic-military interest. This situation was dictated primarily by dynamic industrialization of Europe, which already in the middle of the nineteenth century led to the exacerbation of the struggle for access to the raw materials and especially to sales markets. In the context of the Balkans the essential importance had the rivalry between Austria-Hungary, which was seeking a safe and comfortable way to the port of Thessaloniki, and Russia, which was striving to change the status of Bosporus and the Dardanelles, for ensure grain exports through the Black Sea and the Mediterranean Sea. It must be remembered that the Balkans and Turkey played an equally important role in the economic plans of other powers – Great Britain, France, and from the late nineteenth century also Italy and Germany. An equally important role played by political and military considerations. The entry of great powers in the so-called imperial era greatly influenced the intensification of the competition for the “undisputed leader” in Europe and the range of spheres of influence, and the crystallization of the opposing military-political blocks in the Europe, pay attention of politicians to those European countries, which was created the possibility of blocking the enemy actions and obtain tactical advantage. For obvious reasons, the Balkans have played in this rivalry special role. Although the imposition of all these factors complicated the situation on the Balkan Peninsula, the persistent tension between the great powers created Balkan states and nations the feasibility of their policy plans. Thus, in the era of the Balkan wars, they did not intend to follow the guidelines of European diplomacy, and taken by the great powers the efforts to save peace and acquisition of potential allies did not lead to the expected success, which clearly confirmed the events of WWI.